PENINGKATAN KEWIRAUSAHAAN PADA ANGGOTA PKK RT.2 RW.9 DUSUN KLANDUNGAN DESA LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG - Diana Eka; Tri Wahyu Widodo; Achmad Zaini; Asminah Rachmi (P3M Politeknik Negeri Malang, 2022)
Some of the problems that arise in PKK RT2 RW 9 Dusun Klandungan Landungsari Village are related to entrepreneurship, including: the absence of an entrepreneurial spirit, the absence of entrepreneurial abilities/skills, the absence of field coaches who guide entrepreneurship, and the absence of capital for entrepreneurship. Training is needed to overcome the problems that occur in PKK RT2 RW 9 Dusun Klandungan Landungsari Village in entrepreneurship. The training that needs to be carried out on entrepreneurship includes: increasing entrepreneurial motivation, providing entrepreneurial skills, mentoring in collaboration with competent field supervisors, entrepreneurship capital/equipment assistance.